CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PEMODERASI PENGARUH CAPITAL INTENSITY TERHADAP TAX AGGRESSIVENESS - Sri Lestari Yuli Prastyatini; Uum Helmina Chaerunisak; Rizki Ikhsan Sucipto (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the effect of corporate social responsibility as a moderator of the effect of capital intensity on tax aggressiveness in manufacturing companies. This study uses a quantitative descriptive method with secondary data and as the population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period, with a total sample of 44 companies. The data analysis technique uses multiple linear regression which is equipped with the classical assumption test, T test, F test and determination (R²) using the SPSS 23 program. The results of this study indicate that the capital intensity variable has a significant effect on tax aggressiveness while the corporate social responsibility variable is not able to moderate the interaction between capital intensity variables on tax aggressiveness